2004
DOI: 10.1002/cbdv.200490136
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Investigation of a 14C‐Labelled β3 Tetrapeptide in Rats

Abstract: The solid-phase synthesis and an ADME investigation with albino and pigmented male rats of the doubly 14C-labelled beta/alpha-tetrapeptide derivative Ac-beta3 hTyr-(D)Trp-beta3 hLys-beta3 hThr-lactone (3; Fig. 3) are described. After intravenous (i.v.) and peroral (p.o.) administration of the peptide, its concentration in blood and plasma, its tissue distribution, and the metabolism and the excretion of the peptide were analyzed over a period of up to 7 days post dose. The tetrapeptide in its ring opened form,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 26 publications
(13 reference statements)
0
25
0
Order By: Relevance
“…In a similar fashion, mixed a,b 3 -tetrapeptide analogues of somatostatin can benefit from excellent binding affinities to the hsst 4 receptor, whilst retaining the complete proteolytic stability associated with the related pure b-tetrapeptidic compounds [13]. One such a,b 3 -tetrapeptide has been shown to be bioavailable when administered to rats [63].…”
Section: B-peptidesmentioning
confidence: 99%
“…In a similar fashion, mixed a,b 3 -tetrapeptide analogues of somatostatin can benefit from excellent binding affinities to the hsst 4 receptor, whilst retaining the complete proteolytic stability associated with the related pure b-tetrapeptidic compounds [13]. One such a,b 3 -tetrapeptide has been shown to be bioavailable when administered to rats [63].…”
Section: B-peptidesmentioning
confidence: 99%
“…Such structures can ideally circumvent the limitations imposed by the side chains of the 20 main naturally occurring ␣-amino acid building blocks. Furthermore, the artificial/modified backbone renders most peptidomimetics resistant to degradation enzymes, thereby increasing their stability in vivo (37,40,47). For the group with modified native backbones, several strategies were proposed, most of which are based on the preservation of a secondary structure similar to that of natural AMPs.…”
mentioning
confidence: 99%
“…Very detailed tests have shown that a variety of peptides composed of ␤-amino acids were stable against many different commercially available proteases and peptidases (10,29). Furthermore, first studies on the stability of ␤-peptides in vivo have shown that virtually no degradation was observed when such peptides were administered to rats (42,43). Some ␤-peptides possess antimicrobial activities (4,5,25,38), bind to the human somatostatin receptor (12,21), function as inhibitors of human immunodeficiency virus type 1 replication (39), and inhibit p53-hDM2 interaction (18).…”
mentioning
confidence: 99%